From rules to practices: Assembling natural resource governance in the Peruvian Amazon - (:unkn) unknown (Routledge, 2024)
An assemblage framework improves our understanding of institutional diversity in natural resource governance. Drawing on the ‘practices of assemblage’ perspective of Tania M. Liand actor network theory studies, this chapter conceptualizes assemblage ...
Keywords: Gobernanza de recursos naturales; Amazonía peruana